Future considerations based on the information from Barrter's and Gitelman's syndromes. Issue 1 (January 2017) - Alfandary, Hadas; Landau, Daniel
Abstract : Purpose of review: Bartter and Gitelman syndromes are typical normotensive salt losing hypokalaemic tubulopathies. Their pathogenesis was gradually deciphered in the past 5 decades, first by typical salt balance studies and histopathology, followed by genetic characterization and discovery of the affected different ion channels. Although the different genotypic subtypes were originally thought to show a similar phenotype, important clinical and biochemical differences can now be found. New findings on the regulation of these channels, as well as the recent discovery of newly affected genes, merit an update on this topic. Recent findings: Na-K-2CL cotransporter and NaCl cotransporter, the two main luminal channels in the thick ascending limb and distal convoluted tubule were found to be regulated by Ste 20-related proline alanine-rich kinase and oxidative stress response kinase. Knockout mice to these channels express a Bartter-like phenotype. MAGE-D2 is new gene found to cause severe polyhydramnios and transient postnatal Bartter-like syndrome. Variants in the different channels causing Bartter syndromes/Gitelman syndromes may also confer susceptibility for hypertension or protect against it. Summary: It remains to be determined if polymorphism or epigenetic changes in these genes and proteins may affect salt handling, explaining, apart from Bartter syndromes and Gitelman syndromes, also hypertension or stroke tendency, or both.